Does Emotional Distress Weaken Romantic Bonds? A Semi-longitudinal Study on Psychological Vulnerability and Relationship Satisfaction - Kutuk, Hasan; Satici, Begum; Ince, Murat (SPRINGER, 2025)
The purpose of this study is to examine the mediating role of emotional distress in the relationship between psychological vulnerability and romantic relationship satisfaction. Psychological vulnerability is defined as an individual's low tolerance for stressful situations and tendency to negative thought patterns. Romantic relationship satisfaction refers to the individual's general perception of happiness and satisfaction with their relationship. Previous studies have shown that individuals with high levels of psychological vulnerability experience lower satisfaction in their romantic relationships. In this context, it was thought that emotional distress could mediate the relationship between these two variables. The study was conducted with a semi-longitudinal design by collecting data twice, five months apart. The participants consisted of 310 adults aged between 18 and 61. The data were analyzed using structural equation modeling. The findings showed that psychological vulnerability positively predicted emotional distress, while emotional distress negatively predicted romantic relationship satisfaction. In addition, it was determined that emotional distress played a partial mediating role in the relationship between these two variables. These results reveal that individuals' internal psychological processes affect not only their personal well-being but also their relational dynamics. In particular, it was concluded that emotional distress is an important mechanism in reducing the relationship satisfaction of individuals with high psychological vulnerability. The findings indicate that increasing individuals' awareness of psychological vulnerability and developing their skills to cope with emotional distress can increase satisfaction in romantic relationships.
Keywords: Psychological vulnerability; Emotional distress; Romantic relationship satisfaction; Semi-longitudinal research; Cross-lagged panel model; RELATIONSHIP QUALITY; MODELS; Psychiatry